2011
DOI: 10.1007/s00535-011-0444-4
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of liver stiffness by antiviral therapy in chronic hepatitis B

Abstract: LS was significantly correlated with fibrosis stage in patients with chronic hepatitis B. The reduction of LS by antiviral therapy was significantly correlated with the reduction of hyaluronic acid. Thus, we conclude that LS can be useful to assess the progression and regression of liver fibrosis stage noninvasively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
43
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 38 publications
2
43
1
Order By: Relevance
“…Furthermore, multivariate analysis revealed that longer antiviral therapy duration prior to the initial LSM was associated with an improvement in liver fibrosis. It appears that in cirrhotic CHB patients, the duration of oral NA intake and the amount of viral replication significantly affect the efficacy of antiviral therapy, which is supported by the findings by Osakabe et al (11). The main limitation of the present study was that no liver histology was available for this cohort.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Furthermore, multivariate analysis revealed that longer antiviral therapy duration prior to the initial LSM was associated with an improvement in liver fibrosis. It appears that in cirrhotic CHB patients, the duration of oral NA intake and the amount of viral replication significantly affect the efficacy of antiviral therapy, which is supported by the findings by Osakabe et al (11). The main limitation of the present study was that no liver histology was available for this cohort.…”
Section: Discussionmentioning
confidence: 53%
“…For instance, liver fibrosis improved in 35-38% of lamivudine-treated CHB patients and 36-39% of ETV-treated CHB patients after 1 year (9,10). Long-term ETV treatment (>3 years) attenuated necroinflammatory activity in all patients and reduced liver fibrosis in 57-100% of patients (11,12).…”
Section: Discussionmentioning
confidence: 93%
“…For instance, liver fibrosis has been reported to improve in 35-38% of lamivudine-treated CHB patients and 36-39% of ETV-treated CHB patients after one year (12,13). Long-term ETV treatment (>3 years) attenuated necroinflammatory activity in all patients and reduced liver fibrosis in 57-100% of patients (1,14). Furthermore, advanced liver fibrosis was shown to be reversed after long-term antiviral treatment (14,15).…”
Section: Discussionmentioning
confidence: 98%
“…The ultimate goal for treating CHB is to block the advancement of chronic liver injury to the stages of cirrhosis, hepatic decompensation and/or hepatocellular carcinoma (HCC). Thus, an early and accurate diagnosis of fibrosis stages is important for assessing prognosis (1)(2)(3).…”
Section: Introductionmentioning
confidence: 99%
“…[15] Antiviral therapy is also one of the important means to delay and reverse liver fibrosis induced by chronic hepatitis B. [16] Adefovir Dipivoxil, as an antiviral agent of nucleoside commonly used in clinic, has a strong role in inhibiting HBV-DNA replication, [17] and it can reduce liver inflammation, promote the recovery of liver function and prevent liver fibrosis progression, and its resistance rate is low. [18] In 2007, in the CBH Prevention Guide proposed by the American Association for the Study of Liver Diseases (AASID), moderate to severe inflammation or obvious liver fibrosis shown by liver biopsy is recommended as one of the indications of antiviral therapy.…”
Section: Discussionmentioning
confidence: 99%